Work, Welfare, and Child Maltreatment - Paxson, Christina; Waldfogel, Jane (Journal of Labor Economics, 2002)
We examine how child maltreatment—including neglect, physical and sexual abuse, and other forms of maltreatment—is affected by parental economic circumstances. Using state‐level panel data on cases of maltreatment and numbers of children in foster care, we find that increases in the fractions of children with absent fathers and working mothers in a state are related to increases in many measures of maltreatment, as are increases in the share of families with two nonworking parents and those with incomes below 75% of the poverty line. Decreases in state welfare benefit levels are associated with increases in foster care placement.